Feasibility exploration of GSH in the treatment of acute hepatic encephalopathy from the aspects of pharmacokinetics, pharmacodynamics, and mechanism - Hu, Kangrui; Xu, Yexin; Fan, Jiye; Liu, Huafang; Di, Chanjuan; Xu, Feng; Wu, Linlin; Ding, Ke; Zhang, Tingting; Wang, Leyi; Ai, Haoyu; Xie, Lin; et al. (Frontiers in Pharmacology, 2024)
Our previous study highlighted the therapeutic potential of glutathione (GSH), an intracellular thiol tripeptide ubiquitous in mammalian tissues, in mitigating hepatic and cerebral damage. Building on this premise, we posited the hypothesis that GSH could be a promising candidate for treating acute hepatic encephalopathy (AHE). To verify this conjecture, we systematically investigated the feasibility of GSH as a therapeutic agent for AHE through comprehensive pharmacokinetic, pharmacodynamic, and mechanistic studies using a thioacetamide-induced AHE rat model. Our pharmacodynamic data demonstrated that oral GSH could significantly improve behavioral scores and reduce hepatic damage of AHE rats by regulating intrahepatic ALT, AST, inflammatory factors, and homeostasis of amino acids. Additionally, oral GSH demonstrated neuroprotective effects by alleviating the accumulation of intracerebral glutamine, down-regulating glutamine synthetase, and reducing taurine exposure. Pharmacokinetic studies suggested that AHE modeling led to significant decrease in hepatic and cerebral exposure of GSH and cysteine. However, oral GSH greatly enhanced the intrahepatic and intracortical GSH and CYS in AHE rats. Given the pivotal roles of CYS and GSH in maintaining redox homeostasis, we investigated the interplay between oxidative stress and pathogenesis/treatment of AHE. Our data revealed that GSH administration significantly relieved oxidative stress levels caused by AHE modeling via down-regulating the expression of NADPH oxidase 4 (NOX4) and NF-κB P65. Importantly, our findings further suggested that GSH administration significantly regulated the excessive endoplasmic reticulum (ER) stress caused by AHE modeling through the iNOS/ATF4/Ddit3 pathway. In summary, our study uncovered that exogenous GSH could stabilize intracerebral GSH and CYS levels to act on brain oxidative and ER stress, which have great significance for revealing the therapeutic effect of GSH on AHE and promoting its further development and clinical application.